Moderating Role Of Career Development In The Relationship Between Career Plateuing And Work Outcomes - Hassan, Mat Sani (2007)
This study examined the moderating role of Career Development Factors on the relationship between Career Plateuing, as the dependent variable, and Work Outcomes, as the independent variables, among Administrative and Diplomatic Officers (ADOs) in Malaysia. Career Development Factors that consist of three variables of Job Performance, Individual Career Management, and Manager’s Roles whereas Work Outcomes variables include Job Satisfaction, Organizational Commitment, Intention to Quit, and Job Involvement. Career Plateuing is operationalized in two dimensions: as objective and subjective events. Objective Career Plateau was measured by job tenure in which employees were considered in plateaued career if they were still maintain the same position without any promotion more than five years and above. Subjective Career Plateau was measured by perceptual questions on their future career. Career Plateau Moderator Model developed by Chay et al. (1995) and Tremblay & Roger (2004), associates with theoretical framework of Nachbagauer and Riedl (2002) were used as the theoretical foundation of this study. This Model explained the effects of Career Development Factors on the relationship between Career Plateau and Work Outcomes for both career dimensions. This study used correctional research design. The study used Proportionate Stratified Random Sampling technique to get a sample of respondents. Data were obtained from 137 Administrative and Diplomatic Officers (ADOs) out of 150 respondents selected from three Central Agencies consists of Prime Minister Department, Public Service Department and Ministry of Finance. The analyses used were central tendency statistics, t-test, Pearson Product Moment Correlation and Moderated Multiple Regression for Categorical Variables (MMR). Analysis showed that 51% Administrative and Diplomatic Officers (ADOs) were found as Objective Career Plateau employees and 55.4% were identified as Subjective Career Plateau employees. Findings showed there were significant differences between plateued and non-plateued Officers for both Objective Career Plateau and Subjective Career Plateau in terms of Work Outcomes. There is a positive and significant relationship between Objective Career Plateau and Intention to Quit but not with the rest of Work Outcomes variables. On the other hand, there is a negative and significant relationship between Subjective Career Plateau with Work Outcomes variables as total, with Job Satisfaction, Organizational Commitment and positive relationship with Intention to Quit. Results also show that Career Development Factors did not moderate the relationship between Objective Career Plateau and all the Work Outcomes variables. Contradictory with Objective Career Plateau dimension, Subjective Career Plateau indicated moderating role of Career Development Factors in the relationship between Subjective Career Plateau with overall Work Oucomes, Job Satisfaction and Organizational Commitment. The study concludes that Subjective Career Plateau explained more variance than does the Objective Career Plateau in an effort to see the moderating role of Career Development Factors in the relationship between Career Plateau and Work Outcomes. It also suggested that the management should be taken proactive action such as improve the strategic training for employees and retrained as well as improve the performance appraisal and create two way communications in order to reduce the effects of Career Plateau. The study suggests that future research should be conducted on the respondents in different service scheme such as on professional groups in various different work scopes.